2006
DOI: 10.2143/ac.61.1.2005139
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of cardiac abnormalities in female adolescents with anoreexia nervosa after refeeding

Abstract: The adolescent girls with anorexia nervosa had significant structural and functional cardiac abnormalities in comparison to the control group. All these abnormalities were reversible except low R wave amplitude in V6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 22 publications
4
51
0
10
Order By: Relevance
“…AN can be a life-threatening condition due to excessive malnutrition, leading to cachexia and body failure. Morbidity rate of AN is between 5-15%, with patients typically succumbing to cardiac complications, multiple organ failure, secondary infection or suicide (81)(82)(83)(84)(85)(86).…”
Section: Targets Of Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…AN can be a life-threatening condition due to excessive malnutrition, leading to cachexia and body failure. Morbidity rate of AN is between 5-15%, with patients typically succumbing to cardiac complications, multiple organ failure, secondary infection or suicide (81)(82)(83)(84)(85)(86).…”
Section: Targets Of Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…This is speculative, as we were unable to find data correlating BMI and left ventricular mass in healthy adults; however, there are data showing patients with anorexia nervosa have decreased left ventricular mass. 13,14 There are also data in Japanese adolescents showing a positive correlation of the R wave amplitude in V 5 with the LV mass (correlation coefficient: boys, 0.32; girls, 0.27, pb0.001 for each) with better correlations in subjects with less fat. 15 Future echocardiographic assessment of left ventricular mass in healthy subjects over a range of BMIs would be useful to elucidate the mechanism responsible for these voltage drops.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have found BMI to be a significant predictor of QTc duration; 9 however, this correlation is not a universal finding, 32 and other studies only detect a correlation with QT dispersion and LV mass index. 47 Certainly BMI is a guide to the severity of malnutrition, although it is imperfect, and because QT duration is affected by so many factors, the association between BMI and QT may not always be readily apparent, particularly in the context of moderate or minor reductions in BMI. Although QT prolongation in AN is largely reversible with appropriate nutrition, 4,5,32,33 overt autonomic dysfunction (and possibly impaired repolarization reserve) may persist for several years despite adequate refeeding and relative normalization of the BMI.…”
Section: Discussionmentioning
confidence: 99%